2020
DOI: 10.3329/jbcps.v38i0.47446
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Assessment of Doctors Working in a Pandemic Condition in Dhaka Medical College Hospital

Abstract: Introduction: The outbreak of COVID-19 is taking an unprecedented mental toll on health workers worldwide. So it comes as no surprise that the mental well-being of health care workers of Bangladesh too is in serious jeopardy. This survey was aimed to assess the immediate psychological impact on doctors working in largest Covid-19 dedicated facility in Bangladesh, Dhaka Medical College Hospital. Methods: This cross sectional study was conducted in a single-centre with response received from participating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 16 publications
4
10
0
Order By: Relevance
“…In Bangladesh, a survey assessing the psychological states on doctors working in a large COVID-19-dedicated facility in Bangladesh found that around 50 % of the participating doctors experienced symptoms of depression and anxiety (Mahmud et al, 2020). Another study found that anxiety and depression were common among healthcare workers in Bangladesh during the COVID-19 pandemic, with 69.5 % screening positive for anxiety and 39.5 % for depression (Tasnim et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Bangladesh, a survey assessing the psychological states on doctors working in a large COVID-19-dedicated facility in Bangladesh found that around 50 % of the participating doctors experienced symptoms of depression and anxiety (Mahmud et al, 2020). Another study found that anxiety and depression were common among healthcare workers in Bangladesh during the COVID-19 pandemic, with 69.5 % screening positive for anxiety and 39.5 % for depression (Tasnim et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies conducted among Bangladeshi doctors, nurses, and other healthcare workers during this pandemic reported frequent anxiety (20.7-69.5 %), depression (26.5-52.1 %), insomnia (18.6-54.2 %), and psychological distress (41.7-67.7 %) (Ali et al, 2021;Barua et al, 2020;Hasan et al, 2020;Khatun et al, 2021;Mahmud et al, 2020;Tasnim et al, 2021). A recent rapid review shows that presence on frontlines, being younger, and being more junior is associated with an increased risk of psychological distress in healthcare workers during viral outbreaks (Kisely et al, 2020).…”
Section: Coronavirus Disease 2019 (Covid-19mentioning
confidence: 99%
“…Furthermore, healthcare workers were humiliated for providing care to COVID-19 and were asked to isolate and stay away from the community and families to curb the further spread of infection. This imposed enormous psychological distress and fear amongst the health workforce (7).…”
Section: Introductionmentioning
confidence: 99%
“…Generalized anxiety was observed more in females, those older than 30 years, who were married, had higher education and were non-governmental employees (13). Another study was conducted among healthcare workers working in a central public hospital that reported depression and anxiety and insomnia amongst 50 and 55% of the doctors, respectively (7).…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study from Dhaka Medical college hospital, among the physicians dealing with pandemic incidents of insomnia and symptoms of depression and anxiety, was observed [22].…”
Section: The Mental Health Of the Flwsmentioning
confidence: 99%